The influence of pedestrian characteristic on pedestrian speed in urban area: a case study at Jalan Tuanku Abdul Rahman, Kuala Lumpur - F.A. Azizan; N.F.S Thalji; Z.A. Rahman; S. Mansor; M.I. Joohari (Penerbit Universiti Kebangsaan Malaysia, 2024)
Short-distance walking, alone or with additional modes, is efficient. Well-established public transport may increase the number of pedestrians since they prefer walking to work, travel, and shop because cities are connected by activities and locations. However, pedestrian-friendly paths and public transport in Malaysia have received little attention. Large-scale facilities like stadiums, movie theatres, and amusement parks are driving the need for pedestrian facilities. Thus, this study aims to examines the pedestrian characteristic at Jalan Tuanku Abdul Rahman, Kuala Lumpur. To discover significant elements, pedestrian behaviour on sidewalks at the indicated location was quantitatively investigated, taking into account general pedestrian characteristics that affect walking speed, such as age, gender, and trip companion. Using a video camera, pedestrian variables like age, gender, and trip companion were calculated for volume, speed, flow, density, and space during weekday and weekend peak hours. Extracted data were then analysed by using SPSS as a statistical software and the Highway Capacity Manual (HCM 2010) was used to classify pedestrian level of services (LOS). Age, gender, and companionship substantially determine the pedestrian flow and the study’s LOS for pedestrian characteristics ranges from D to E, indicating that Jalan Tuanku Abdul Rahman’s sidewalk relationship varies. This research strongly recommends a dedicated walkway to increase pedestrian space and improve services along Jalan Tuanku Abdul Rahman, Kuala Lumpur. This study will also serve as a guideline to the transport operator into improving the future of pedestrian walkway design facilities.